High Resolution Sonography in Diagnosis of Metastatic Cervical Lymph Nodes in Oral Squamous Cell Carcinoma (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Ultrasound is reported superior to clinical palpation fordetecting lymph nodes and metastasis. The advantage ofultrasound over other imaging modalities is price, lowpatient burden, and possibilities for follow up. A crosssectional Study on 29 cases of oral squamous cell carcinomawas done in Department of Oral & Maxillofacial Surgery,Dhaka Dental College & Hospital, Dhaka from January2006 to December 2007. The sensitivity, specificity, positivepredictive value, negative predictive value & Accuracy ofUltrasonographic technique for determining metastaticcervical lymph node were 93.33%, 50%, 66.7%, 87.5% and72.4% respectively. Considering the finding of the study,Sonographic evaluation can improve the diagnosis ofmetastatic cervical lymph node in patients with oralsquamous cell carcinoma. It is cost effective, non-invasive,less burden to patient, does not create problem ofoverlapping with mandible and can be done repeatedly tofollow up. Therefore, high resolution sonography may bean adjunct tool in diagnosing metastatic nodes in patientswith oral squamous cell carcinoma.DOI: 10.3329/jbcps.v28i2.5369J Bangladesh Coll Phys Surg 2010; 28: 92-99